Extraction of essential oils from Zingiberaceace famili using microwave techniques - Abd Aziz, Nor Azila (2017)
The essential oil from ZingiberaceaceFamili has many potential, especially in medicine, cosmetic and food industries. Therefore, therequirement to get the highest yield as well as good quality of essential oil gives the motivation of this research. Nowadays, the conventional extraction, especially in the commercial factory uses a lot of energy, high cost and a lot of extraction times. To overcome these disadvantages, microwave extraction technique (MET) which known as the best alternative extraction methods in terms of the producing of essential oil at shorter time was used at various extractions process parameters. Besides that, the undertaken in this thesis includes the performance of heating process in terms of the absorption power and the electric field strength. The main goal of this research is to study the various factors using microwave-assisted extraction that influences the production of essential oil in terms of the total yield and the total percentages of the oxygenated compound from Zingiberaceace Family’s essential oil (Java turmeric, Mango ginger, Black turmeric and Turmeric). Laboratory studies were carried out at different factors such as the different power of heating source using microwave-assisted extraction, the amount of water added into the fresh and frozen samples, the soaking time of the sample, and the dry sample with different drying methods. Basically, the sample with solvent (distilled water) was put in the container with a hole on top of the cover and the container will placed inside the Microwave Extraction Laboratory System (MELs) which is the laboratory microwave oven. The distillation unit was connected with the container and the extraction process parameter was controlled by using the terminal controller-personal computer where the EasyWave 3.5 software program was installed. The yield of essential oil was collected and stored until used.For Java turmeric, the unique parameter that gives higher yields (6.37 %) is at the combination of dried sample mixture using an open air drying method, 200 ml of water and 600 W of microwave power heating. For Mango ginger, the unique parameter that gives higher yields (1.22 %) is at the combination of dried sample mixture using the electric oven drying method, 200 ml of water and 600 W of microwave power heating. For Black turmeric, it produces higher yields (1.26 %) with the combination of these unique parameter; dried sample mixture using a microwave oven drying method, 200 ml of water and 600 W of microwave power heating. For Turmeric, the highestyields (2.25 %) were obtained with the combination of these unique parameter; dried sample mixture using an open air drying method, 200 ml of water and 600 W of microwave power heating. This indicates that every sample has its own parameter to produce the highest yield of essential oil and among those samples, the dried sample was found to be a unique parameter that produce high yield. This happens due to the cell wall of the sample’s structures that already destroy and allow the extraction of essential oil easily. The second goal is to analyzechemical compounds, especially the percentage of oxygenated compound. This analysis was using gas chromatography –mass spectrometry (GC-MS) and found that at every experimental order, it reveals the same compound but different abundance. This happens due to the heating conditions as some compounds were very sensitive. Following the optimum parameter that give higher yield of essential oils, the total percentages of oxygenated compound that used to identify the quality of essential oilis at64.16%, 73.24%, 64.54% and 77.20% for Java turmeric, Mango ginger, Black turmeric and Turmeric. That means, among all the sample, the essential oil from Turmeric was estimated to be the best oil compared to others. Every experimental order successfully extracted the compounds known to have many advantages such as antimicrobial, analgesic, and antifungal like cedr-8-ene, ar-curcumene, camphor, caryophylleneoxide, α-curcumene, eucalyptol, ar-turmerone, curlone and turmerone. The third goal was comparing theperformance of the extraction microwave method (solvent free microwave extraction, SFME and microwave-assisted extraction, MAE) and conventional method (Hydro-distillation, HD)in terms of the yield and the percentages of oxygenated compound.The extraction was done in one combination of extraction process parameter. Microwave-assisted extraction method was determined to give the best result in terms of the total yieldas water assist in the extraction process. However, the hydro-distillation was found to produce high percentage of oxygenated compound. These indicate that different techniques of extraction play an important role in the production of essential oil. From the research, microwave-assisted extractionwas revealed as a best extraction method in terms of the producing the total yield of essential oil and as many factors influencing the production of essential oil, the result of the combination of extraction process parameter can be used for further research. The extraction process parameter does not affect the compound in the essential oil, but affect the total abundance. This happens due to the compound that very fragile and vanishes at certain condition.